2013
DOI: 10.1093/dnares/dst006
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Gut Microbiota of Healthy Adults in Response to Probiotic Intervention Revealed by High-Throughput Pyrosequencing

Abstract: Probiotics are live microorganisms that potentially confer beneficial outcomes to host by modulating gut microbiota in the intestine. The aim of this study was to comprehensively investigate effects of probiotics on human intestinal microbiota using 454 pyrosequencing of bacterial 16S ribosomal RNA genes with an improved quantitative accuracy for evaluation of the bacterial composition. We obtained 158 faecal samples from 18 healthy adult Japanese who were subjected to intervention with 6 commercially availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
284
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(291 citation statements)
references
References 69 publications
5
284
1
1
Order By: Relevance
“…The finding is in agreement with several probiotic intervention studies, where limited changes in overall structure of fecal microbiota were observed both in children (Larsen et al, 2011;Nylund et al, 2013) and in adults (Gerritsen et al, 2011;Kim et al, 2013;Lahti et al, 2013). The increased stability of Actinobacteria in the treatment group may have been caused by inulin, which is known to support the growth of bifidobacteria, the main group within the phylum, in the intestine (Veereman, 2007;Salazar et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The finding is in agreement with several probiotic intervention studies, where limited changes in overall structure of fecal microbiota were observed both in children (Larsen et al, 2011;Nylund et al, 2013) and in adults (Gerritsen et al, 2011;Kim et al, 2013;Lahti et al, 2013). The increased stability of Actinobacteria in the treatment group may have been caused by inulin, which is known to support the growth of bifidobacteria, the main group within the phylum, in the intestine (Veereman, 2007;Salazar et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…In a recent intervention study that was performed adopting the same trial design (6), the administration of capsules containing the probiotic strain Lactobacillus paracasei DG did not modify the ␣-diversity of participants' fecal samples, but, in contrast to the results of this study, induced a significant change in the ␤-diversity in terms of weighted UniFrac distances. Kim et al (34) did not observe significant alterations in ␣-and ␤-diversities following the consumption of various probiotic products; however, a very limited number of subjects per group (only three) were used in that study. Furthermore, no alterations in ␣-and ␤-diversities were observed in the fecal microbiota of 1-to 2-year-old children following the consumption of probiotic milk containing Lactobacillus rhamnosus GG (LGG), Lactobacillus acidophilus La-5, and Bifidobacterium animalis subsp.…”
Section: Discussionmentioning
confidence: 80%
“…Although their numbers then fell to the pretest level, this 'transient colonization' also means that they are safe to consume 32 . A recent study by Kim et al used pyrosequencing to examine the composition of the intestinal microflora in individuals receiving probiotics 33 , and the results did not reveal any significant changes. As healthy microflora are fairly robust and not easily altered, short-term supplementation of probiotics may have limited capability to modify the intestinal microflora.…”
Section: Parameter † Baselinementioning
confidence: 98%